Simultaneously mechanically flexible, photobending, and acidochromic cyanostilbene molecular crystals - Parthasarathy, Thiyagaraj; Mishra, Manish Kumar; Bhattacharya, Biswajit; Emmerling, Franziska; Ghosh, Soumyajit (Crystal Growth & Design, 2024)
Molecular crystals that respond to multiple stimuli are gaining significant attention for their potential in smart materials like actuators and sensors. However, imparting multiple stimuli-responsive properties to a single crystal remains a major challenge. Herein, we report two cyanostilbene derivative-based crystals 1 and 2, with various responses to stimuli such as mechanical stress, light, acid vapors, etc. Both crystals 1 and 2 demonstrated mechanical flexibility and reversible acidochromism. Additionally, crystal 1 also exhibited light-induced photobending, which is ascribed to Z to E photoisomerization. Detailed structure-property correlation was established to unravel distinct mechanical responses. The development of these multitasking crystals may find applications in multitasking actuators, anticounterfeiting materials, and more.

Helically twistable cyanoacrylate crystal with simultaneous photomechanical bending - Parthasarathy, Thiyagaraj; Bhowmik, Aritra; Mishra, Manish Kumar; Ghosh, Soumyajit (Chemical Communications, 2026)
A cyanoacrylate derivative crystal exhibits an unusual combination of one-dimensional elasticity, plasticity, and reversible hand-held twisting. Twisting induces a reversible single crystal to polycrystal transition. It also displays photobending via a cycloaddition reaction under 365 nm irradiation and thermally recovers its original state, retaining functionality in the twisted state, indicating potential applications in soft robotics and smart actuators.

Reversible twisting-induced crystalline-polycrystalline transformation in cyanoacrylate crystals - Parthasarathy, Thiyagaraj; Bhowmik, Aritra; Bhattacharya, Biswajit; Mishra, Manish Kumar; Ghosh, Soumyajit (Chemical Communications, 2026)
We report cyanoacrylate-based organic crystalline materials that exhibit reversible hand-induced helical twisting through the combined action of 1D elasticity and 2D plasticity. These crystals twist and untwist without lattice damage, retaining their elastic integrity through pi slip-stacking and Cl & ctdot;Cl, C-H & ctdot;Cl, and Me & ctdot;Me interactions. Their unique integration of elastic recovery, plastic bending, and reversible twisting highlights their potential as mechanically adaptive materials for flexible and responsive devices.